Giant dielectric behaviour of CaCu3Ti4O12 subjected to post-sintering annealing and uniaxial stress - Prasit Thongbai (2018)
This paper reports the influences of the post-sintering annealing in argon and uniaxial compressive pre-stress on the giant dielectric properties of the CaCu3Ti4O12 ceramics sintered at 1100 °C in air for 6 and 16h. The CaCu3Ti4O12 ceramic sintered at 1100 °C for 6h exhibited high ε′ of ∼1 × 104 whereas the CaCu3Ti4O12 ceramic sintered at 1100 °C for 16h possessed one order of magnitude higher dielectric constant (ε′∼2 × 104). The dielectric behaviour of both samples exhibits Debye-like relaxation, and can be explained based on a Maxwell-Wagner model. Post-sintering annealing in argon for 5h leads to a significant increase in ε′ for CaCu3Ti4O12 ceramic sintered at 1100 °C for 16h but a slight decrease in ε′ for the CaCu 3Ti4O12 ceramic sintered at 1100 °C for 6h. The ε′ of the 16h sintered CaCu3Ti 4O12 ceramic after annealing in argon increases with increasing temperatures, and exhibits a peak at about 150 °C, which is closely related to the oxygen vacancies. The dielectric behaviour of this argon-annealed sample follows the UDR law. The dielectric properties of the argon-annealed samples change significantly with the applied compressive stress (the absolute change can reach 25% at a maximum stress of 130MPa). However, the changes in dielectric properties with the stress in the samples subjected to different sintering times follow opposing trends. The mechanisms responsible for this difference are discussed. © 2007 IOP Publishing Ltd.